Investigation the Transformations Regularities of Stable Gas CondensateHydrocarbons during Their Processing on Zeolite Catalysts; Mechanisms of Catalytic Reactions (MCR-XI) - Bogdanov I. A. Ilya Aleksandrovich (2019, 2019)
Title screen